How mobility as a service impacts public transport business models - Corinne Mulley; John D. Nelson (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
To be successful, Mobility as a Service (MaaS) will need a model that can accommodate public and private transport providers in a financially sustainable way. This paper discusses MaaS systems led by the government and by the market. How can different business models provide better mobility for citizens, while also delivering on other objectives? The paper considers different methods of financing public transport operators and alternative ways of supporting services with subsidies. It concludes with a discussion of the possible long-term impacts of Covid-19 and the disruptive potential of autonomous vehicles in public transport.
Keywords: 330; Öffentlicher Verkehr; Mobilität; Geschäftsmodell; Autonomes Fahrzeug; Coronavirus; Dienstleistungsqualität